Treatment of retained fetal membranes in dairy cows - A.S. Asker; H. A. Dakheel (Kufa Journal for Veterinary Medical Sciences, 2015)
Treatments of retained fetal membranes in dairy cattle.The study was conducted on 100 dairy cows of Friesian-Holstein breeds suffering from retained fetal membranes, presented in Al-Fayhaa station, at Gabala, Musaib-Babel. The age of animals ranged from 4-8 years. The animals were divided into four equal groups, each groups contain 25 cows.The first group were treated with 22,5mg of PGf2 I.M, The second group treated with 100 i.u of oxytocin i.m. The 3rd group was treated with 50 i.u. of oxytocin .while the fourth group treated with 5mg estradiol benzoate i.m. The animals were under observation within 72 hours after treatment, to follow expulsion of fetal membranes.